A Corpus Study Of The Swahili Demonstrative Position - Mwamzandi, Mohamed (My University, 2018)
Synchronic studies on Swahili adnominal demonstratives have not addressed the interplay between syntactic position and pragmatic function of these structures. This study shows how referential givenness of discourse entities may explain Swahili word order variation in Swahili adnominal demonstratives. Class 1 (animate nouns) demonstratives are examined in the two attested word orders: NP+DEM and DEM+NP. A close analysis of dataset extracted from the Helsinki Corpus of Swahili reveals that the two structures have distinct pragmatic values. The NP+DEM order is used for active topics while the DEM+NP order reactivates semiactive/inactive topics. This study reveals how the syntax-pragmatics interplay may explain distinct structures viewed as semantic equivalents by native speakers.
Keywords: Swahili; corpus study; adnominal demonstratives